2018
DOI: 10.1177/0218492318798258
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical outcome in isolated prosthetic mitral valve endocarditis

Abstract: Background Most previous studies dealing with predictors of surgical outcome in prosthetic valve endocarditis included patients with aortic and/or mitral valve prostheses. Here, we concentrate on isolated prosthetic mitral endocarditis due to heterogeneity of epidemiological data, anatomical factors, and surgical techniques between mitral, prosthetic mitral, and aortic endocarditis between prosthetic mitral and prosthetic aortic endocarditis. Methods Data of 40 patients reoperated upon due to isolated prosthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…(95% CI 0•5-2•4) of patients (appendix p 24). In children, 44•7% (95% CI 29•5-60•5) of patients with infective endocarditis had congenital heart disease and 26•0% (10•2-45•9) had rheumatic heart disease as underlying cardiac conditions (appendix pp 27-28).21 (50%) of 42 studies reported on clinical and echocardiographic features of infective endocarditis [21][22][23][24][25][26][27][29][30][31][32][33][34][35]38,39,[43][44][45][46]52. These data are summarised in…”
mentioning
confidence: 99%
“…(95% CI 0•5-2•4) of patients (appendix p 24). In children, 44•7% (95% CI 29•5-60•5) of patients with infective endocarditis had congenital heart disease and 26•0% (10•2-45•9) had rheumatic heart disease as underlying cardiac conditions (appendix pp 27-28).21 (50%) of 42 studies reported on clinical and echocardiographic features of infective endocarditis [21][22][23][24][25][26][27][29][30][31][32][33][34][35]38,39,[43][44][45][46]52. These data are summarised in…”
mentioning
confidence: 99%
“…There are currently no validated scoring models to predict in-hospital complications or outcomes of IE. Current models have focused on long-term outcomes and complications after cardiac surgery [23][24][25]. As demonstrated in this study, the CHA 2 DS 2 -VASc score may serve as a risk assessment tool in patients with IE.…”
Section: Discussionmentioning
confidence: 83%
“…Title and abstract screening of the remaining 756 papers led to further exclusion of 675 papers that did not meet our eligibility criteria. Subsequently following full text screening of the 81 papers, only 31 papers were included in the study that met our eligibility criteria 16–46 . The screening process is shown in the PRISMA flow chart in Figure 1.…”
Section: Resultsmentioning
confidence: 99%